Interdecadal variation in aerosol optical properties and their relationships to meteorological parameters over northeast China from 1980 to 2017. (May 2020) - Zhao, Hujia; Che, Huizheng; Gui, Ke; Ma, Yanjun; Wang, Yaqiang; Wang, Hong; Zheng, Yu; Zhang, Xiaoye
Abstract: Northeast China has undergone rapid urbanisation with increased anthropogenic emissions, and the types and absorption properties of aerosols may affect regional climate change. MERRA-2 (Modern-Era Retrospective analysis for Research and Applications, version 2) distributions of aerosol optical depth (AOD), Ångström exponent (AE), and absorption aerosol optical depth (AAOD) from 1980 to 2017 was studied to estimate the climatology of aerosol optical properties over Northeast China. The highest AOD and AAOD occurred in Liaoning Province range from 0.3 to 0.4 and 0.02–0.03, respectively. The spacial distribution of black carbon (BC) AOD was similar to AAOD with maximum value in Liaoning province about 0.04 related to the emission sources and human activities. The seasonal interdecadal distribution indicated larger dust (DU) AOD in Liaoning (0.12) and organic carbon (OC) AOD in Heilongjiang (0.18). The contribution of SO4 to total AOD was significant in autumn and winter, and BC particles contributed 70% to total AAOD in all seasons. The decadal change in AOD was positive for 2000–2009 (0.2/decadal) due to the increased dust events happening in spring. The positive correlation between AOD and relative humidity (RH) at surface was about 0.4–0.6; the negative correlation between AOD and surface wind speed (WS) (−0.6), planetary boundary layer height (PBLH) (−0.2 to −0.6), sea level pressure (SLP) (−0.2) was found over the study period. This study's findings enable more comprehensive understanding of the distribution of aerosols optical properties and regional climatology in Northeast China. Highlights: Higher interdecadal AOD andAAOD wereobviouslyfound in Liaoning Province. The contribution of SO4 and BC was significantto total AOD and AAOD. Meteorological factors havelarge influence on regional aerosol extinction.